2021
DOI: 10.3390/agronomy11112149
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Economic Response of Modern Cotton Cultivars to Nitrogen Fertilizer

Abstract: Non-optimal application of nitrogen (N) fertilizer in cotton (Gossypium hirsutum L.) production systems often results from a producer’s uncertainty in predicting the N rate that ensures maximum economic return. Residual soil nitrate-N (NO3-N) is also often unaccounted for in fertilizer management decisions. In this study, the lint yield and profitability of two cotton cultivars (FiberMax FM 958 and Deltapine DP 1646 B2XF) were compared across five N fertilizer treatments [0 kg ha−1 (control), 45 kg ha−1 (N-45)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Typically, cotton yield increases with an increase in N fertilizer until it reaches an optimum level, beyond which additional N fertilizer does not affect yield and most probably results in wasted expenses and negatively impacts soil health [50,51]. The obtained data of the study showed that the reduction of the fertilizers to the half dose recommended did not affect either yield or technological parameters and are in accordance with [13,52], who proposed that cotton productivity is highly dependent on a cultivar's genetics and highlighted that N fertilizer application rates could be reduced based on updated crop requirements, without yield penalty due to the different requirements of newer cotton cultivars.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Typically, cotton yield increases with an increase in N fertilizer until it reaches an optimum level, beyond which additional N fertilizer does not affect yield and most probably results in wasted expenses and negatively impacts soil health [50,51]. The obtained data of the study showed that the reduction of the fertilizers to the half dose recommended did not affect either yield or technological parameters and are in accordance with [13,52], who proposed that cotton productivity is highly dependent on a cultivar's genetics and highlighted that N fertilizer application rates could be reduced based on updated crop requirements, without yield penalty due to the different requirements of newer cotton cultivars.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, nitrogen is a critical element for cotton growth and development [13] and nitrogen fertilization has significant impacts on cotton growth, boll development, lint yield, and fiber quality [14]. Nitrogen fertilizer has been shown to significantly impact cotton growth, affect the physiological characteristics of cotton, and eventually determine the final yield and quality.…”
Section: Introductionmentioning
confidence: 99%
“…'s (2023) investigation found that irrigation had no impact on total node count at FB. However, previous research tested N fertilizer, which significantly influenced total nodes (Main et al., 2013; Pabuayon et al., 2021; Shah et al., 2021). Regardless of the SMU, the year 2016 exhibited the lowest node count, ranging between 10 and 13 nodes per plant.…”
Section: Resultsmentioning
confidence: 99%
“…Total N applications averaged 82, 102, and 114 kg ha -1 for the 33%, 66%, and 100% irrigation levels, respectively, across the three study years. Applications of N at greater than optimal rates at given irrigation levels were avoided to prevent vegetative growth and diminished availability of assimilates required for fruiting structure development that would reduce yield potential (Main et al, 2013;Pabuayon et al, 2021).…”
Section: Field Experimentsmentioning
confidence: 99%